EXPOSURE MODELLING IN RISK ASSESSMENT OF INDUSTRIAL ENTERPRISES - Franchuk, Grigory М.; Radomska, Мargaryta М. (Proceedings of National Aviation University (archive), 2009)
The provisions and theory of exposure assessment are presented in the article. According to basic directions of exposure assessment methods and necessary data are defined. The elements of exposure modeling for different environments and systems of human body are developed. Practical application of exposure and dose definition to the process of environmental risks assessment process is given.